The necessity of implementation the energy efficiency measures at the industrial enterprises - Koziuk, Olha; Tytarchuk, Dmytro (Management and Entrepreneurship: Trends of Development, 2018)
The relevance of the research is the necessity to increase the level of energy conservation at domestic industrial enterprises by introducing a system for managing energy resources to reduce production costs through efficient use of energy resources. The energy efficiency of individual industries and the economy of the country in general is positioning today as a key criterion for securing energy security and competitiveness in the world market and is one of the main factors, which determines the investment attractiveness in economy. Purpose. Research of introduction of a systematic approach to energy saving management and provision of recommendations on its implementation at industrial enterprises of Ukraine. Design/methodology/approach. System-defined and comparative methods and structural-functional approaches. Findings: the necessity of using energy saving measures that will significantly reduce the cost of energy. Research limitations/implications. A study the process of development of enterprises taking into account the peculiarities of development of activities in the sphere of energy saving. Originality/value. Such knowledge will help to increase the profitability and competitiveness of manufacturing enterprises.